2023
DOI: 10.1111/fare.12848
|View full text |Cite
|
Sign up to set email alerts
|

Familial roles and support of doctoral students

Abstract: ObjectiveIdentify the role(s) and support(s), if any, that family members provide to first‐generation and historically marginalized doctoral students, including strengths and challenges of this support.BackgroundNonfinancial family support is important for the success and retention of first‐generation and historically marginalized graduate students. More empirical studies of the role(s) and support of family members of these doctoral students are needed.MethodDuring an intervention designed for first‐generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…A meta-analysis by Kim et al ( 2020 ) concluded that parents’ engagement and involvement show a powerful positive impact on the student’s academic achievement and motivation. Other studies found parents’ support as significant in the student’s academic adjustment and achievement also in higher education (e.g., Dorrance et al, 2020 ; Walsh et al, 2023 ). Fass and Tubman ( 2002 ) reported positive parent-student attachment as a relevant protective factor in university students.…”
Section: Introductionmentioning
confidence: 95%
“…A meta-analysis by Kim et al ( 2020 ) concluded that parents’ engagement and involvement show a powerful positive impact on the student’s academic achievement and motivation. Other studies found parents’ support as significant in the student’s academic adjustment and achievement also in higher education (e.g., Dorrance et al, 2020 ; Walsh et al, 2023 ). Fass and Tubman ( 2002 ) reported positive parent-student attachment as a relevant protective factor in university students.…”
Section: Introductionmentioning
confidence: 95%
“…Cohen (2011), for example, maintained that students who had to juggle the needs of their families such as assisting their children with schoolwork, were at greater risk of non-completion as were students who experienced difficult family relationships (Schmidt & Hansson, 2018). Other findings to emerge are how well-integrated (Rochinson-Szapkiw et al, 2016) and how well-informed students' families are about what doctoral study entails (Breitenbach et al, 2019;Walsh et al, 2023). These findings have led researchers (e.g., Breitenbach et al, 2019;Rochinson-Szapkiw et al, 2016;Walsh et al, 2023) to conclude that there is a need for universities to provide resources to support both the education and the integration of doctoral students' families.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Other findings to emerge are how well-integrated (Rochinson-Szapkiw et al, 2016) and how well-informed students' families are about what doctoral study entails (Breitenbach et al, 2019;Walsh et al, 2023). These findings have led researchers (e.g., Breitenbach et al, 2019;Rochinson-Szapkiw et al, 2016;Walsh et al, 2023) to conclude that there is a need for universities to provide resources to support both the education and the integration of doctoral students' families.…”
Section: Review Of the Literaturementioning
confidence: 99%